The political economy of coal: Lessons learnt from 15 country case studies. (December 2021) - Steckel, Jan C.; Jakob, Michael
Abstract: This article summarizes lessons learnt from 15 case studies on the political economy of coal following one integrated framework. It proposes four country categories that show comparable properties to analyze the political economy of coal, including countries that i) phase out coal, ii) phase in coal, iii) are established users and iv) depend on coal exports. Regarding the prevalence of coal investments in many countries, it highlights the role of conflicting societal objectives, e.g. affordable electricity prices being more important than environmental targets. Vested interests are mainly related to locally concentrated job losses, expectations regarding regional development, coal royalties, as well as lobbying by a politically well-connected coal industry. Those factors can be either strengthened or extenuated by structural factors, including multi-level governance issues and the structure of the energy market. Entry points for policy vary for different country categories. De-risking financing of alternatives to coal as well as reforms of energy markets are most important entry points in countries that still invest in coal or plan to phase in coal to their energy systems.